Smoke Free Regulation for Clean and Healthy Evironment in Blitar District Indonesia - Sri Widati; Santi Martini; Kurnia Dwi Artanti; Hario Megatsari; Priyono Adi Nugroho; Amer Siddiq Amer Nordin (Universitas Airlangga, 2024)
Introduction: The implementation of smoke-free regulations is an effort to create a clean and healthy environment in the Blitar District, Indonesia. The main purpose of this research is to analyze public opinion on the smoke-free regulations drafting in the Blitar District. Methods: To analyze public opinion about the smoke-free regulations, we used a cross-sectional design with a RAPID survey conducted in 2015. The research involved distributing questionnaires to 1,008 respondents, with the sample size proportionally divided across 22 districts. For the implementation of the regulation, we conducted observational research over four years. The effort to draft the smoke-free regulations continued until 2019, and the implementation of the regulations is ongoing until 2023. Results and Discussion: Results showed that 94.5% supported the regulations. The RAPID survey results provided evidence for drafting the smoke-free regulations. This evidence was used to advocate for stakeholder support in drafting and implementing the regulations in the Blitar District. Although the smoke-free regulations were released in 2019, their implementation has been very challenging and requiring significant effort. Conclusion: A RAPID survey showed that almost all people in Blitar support the drafting and implementation of the smoke-free regulations. The implementation requires significant effort to ensure it proceeds smoothly and needs support from all stakeholders in the Blitar District.